LOCAL GOVERNMENT: WORKING GROUPS PROMOTE AND MONITOR THE ACTIVITIES OF EXECUTIVE BODIES - V. Souponitsky (Вестник университета, 2016)
The article analyzes the possibilities of using a previously proposed working groups promote and monitor the activities of Executive bodies (RGSC) in local government, particularly when dealing with complicated concerns of a significant portion of the population of the region. Examines the legal framework of RGSC, the tasks that can be solved by RGSC. Looks at the possible role RGSK in the electoral process at the level of MS and evaluated the potential results RGSC. Offers the best option of using RGSC in the interests of the population in the form of an all-Russian program "Development of mechanisms for the formation and establishment of a network of working groups promote and monitor the activities of Executive bodies on the territory of the Russian Federation" with a preliminary pilot project on the territory of Moscow and Sevastopol.